Nicotinamide Nucleotide Transhydrogenase (Nnt) is Related to Obesity in Mice - Kunath, Anne; Heiker, John T.; Kern, Matthias; Kosacka, Joanna; Flehmig, Gesine; Stumvoll, Michael; Kovacs, Peter; Blüher, Matthias; Klöting, Nora (Hormone and Metabolic Research, 2020)
The C57BL/6J (B6J) mouse strain has been widely used as a control strain for the study of metabolic diseases and diet induced obesity (DIO). B6J mice carry a spontaneous deletion mutation in the nicotinamide nucleotide transhydrogenase (Nnt) gene eliminating exons 7–11, resulting in expression of a truncated form of Nnt, an enzyme that pumps protons across the inner mitochondrial membrane. It has been proposed that this mutation in B6J mice is associated with epigonadal fat mass and altered sensitivity to diet induced obesity. To define the role of Nnt in the development of diet induced obesity, we generated first backcross (BC1) hybrids of wild type Nnt C57BL/6NTac and mutated Nnt C57BL/6JRj [(C57BL/6NTac×C57BL/6JRj)F1×C57BL/6NTac]. Body weight gain and specific fat-pad depot mass were measured in BC1 hybrids under high fat diet conditions. Both sexes of BC1 hybrids indicate that mice with Nnt wild type allele are highly sensitive to DIO and exhibit higher relative fat mass. In summary, our data indicate that the Nnt mutation in mice is associated with sensitivity to DIO and fat mass.
Keywords: diet-induced obesity; genetic background; visceral fat mass; C57BL/6; Nnt; DIO